Cutis verticis gyrata: Three cases illustrating three different etiologies. Issue 5 (18th May 2022) - Chamli, Amal; Jones, Meriem; Bacha, Takwa; Litaiem, Noureddine; Zeglaoui, Faten
Abstract: Cutis Vertcis gyrata is an uncommon neurocutaneous syndrome characterized by excessive growth of the skin of the scalp or the face, forming folds of similar aspect to cerebral cortex gyri. Three categories have been individualized: the primary form, essential or non‐essential, and the secondary form. Abstract : Cutis verticis gyrata is a rare neurocutaneous syndrome with mainly anesthetic impact. A rigorous clinical examination with a minimal workup is required to eliminate a secondary or a primary non‐essential form and to assess interdisciplinary management.